Completion and Factors Associated with Maternity Continuum of Care among Mothers Who Gave Birth in the Last One Year in Enemay District, Northwest Ethiopia - Anguach Shitie; Nega Assefa; Merga Dhressa; Tenagework Dilnessa (Journal of Pregnancy)
Background. Ethiopia still suffers high levels of neonatal and maternal mortality, so the maternity continuum of care is a continuous framework for the delivery of maternal care from pregnancy to the postnatal period. Skilled care during pregnancy, childbirth, and the postpartum period is an important intervention in reducing maternal and neonatal morbidity and mortality. But in Ethiopia, there are limited studies on the completion of the maternity continuum of care, so this study will help to suggest interventions in order to reduce the dropout of the maternity continuum of care. Objective. To assess the completion of the maternity continuum of care and factors associated with it among mothers who gave birth in the last one year in Enemay District, Northwest Ethiopia. Method and Materials. A community-based cross-sectional study was conducted from February 25 to March 10, 2019, on 651 women who gave birth in the last one year. The data were collected by a face-to-face interview through pretested and structured questionnaires. Binary logistic regression was used to identify predictors of the completion of the maternity continuum of care. Variables with a P value < 0.05 in multivariable analysis were declared as statistically significant associated factors. Results. This study revealed that about 45% (95% CI: 40.9%, 48.8%) of respondents completed the continuum of care. Women with secondary education (AOR=6, 95% CI: 2.26, 16.6), women whose occupation is farming (AOR=0.18, 95%, CI: 0.1, 0.32), women who have autonomy in health care decision (AOR=4, 95% CI: 2.26, 7.2), women who have exposure to media (AOR=1.97, 95% CI: 1.2, 3.27), women with wanted pregnancies (AOR=3.33, 95% CI: 1.87, 5.9), para five and above women (AOR=2.85, 95% CI: 1.28, 6.3), and women whose husbands are employed (AOR=4.97, 95% CI: 1.16, 21.2) were significantly associated with the completion of the maternity continuum of care. Conclusions and Recommendation. This study showed that less than half of the participants had achieved the continuum of care and education level, and both respondents and their husband’s occupation, parity, autonomy in health care decision, exposure to the mass media, and wantedness of pregnancy were associated with the completion of the maternity continuum of care; therefore, working on enhancing the capacity of women’s autonomy in health care and decision-making and preventing unintended pregnancy helps to improve the completion of the maternity continuum of care.